A Clinicopathological Study on Cases of Hodgkin’s Diseases in IraqiChildren Attending AL-Kadhimiyia Teaching Hospital - Abbas, Sawsan S. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Hodgkin’s Diseases is a group of cancers characterized by Reed- Sternberg cells, aneuoploid cells that usually express CD15 and CD30. Several epidemiological and serological studies support the role of Epstein –Barr virus in the pathogenesis of Hodgkin’s DiseasesPatients and Method: A retrospective study was done where by twenty cases were collected from the Pediatric Oncology Clinic in AL-Kadhyimia Teaching Hospital over a period of five years from the first of January 2002 – end of December 2006.Information was taken from the patient’s records in the Pediatric Oncology Clinic including age at presentation, sex, physical finding, histopathological subtypes, staging , treatment applied , outcome and follow upResults: Among the studied group 14 cases ( 70%) were males and 6 cases (30%) were females , male : female ratio equal to 2.3:1, rang of age was between 5- 16 years with a peak age at presentation was between 11- 15 years. The initial presentation was an enlarged cervical lymph node in 18 cases ( 90%), histopathologically , most of the patients had mixed cellularity subtype , 9 cases (45%), stage II and stage III comprise the majority of cases 8 cases for each (40%), B symptoms were reported in 13 cases ( 65%) . Chemotherapy was the mainstay of treatment with good response. The overall survival was (90%), 18 cases over a median period of follow up of 2-5 years. One case relapses two months after the end of treatment, no death.Conclusion: Although mixed cellularity was encountered in most of our patients but the response to chemotherapy is good.